2021
DOI: 10.1097/scs.0000000000007962
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Extra Craniofacial Abnormalities in Patients With Craniofacial Microsomia

Abstract: Introduction: Craniofacial microsomia (CFM) is caused by abnormalities in the development of the first and second pharyngeal arches. One-third to half of the patients with CFM also present with extra craniofacial (ECF) malformations. The knowledge of the visceral alteration related to CFM is vital for optimized care and a better prognosis. Aim: To describe the incidence of ECF malformations in patients with CFM and to infer if there was a correlation between CFM and ECF malformations. Materials and Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Heart malformation (15.3%), spine, chest, limb, and finger malformations (7.4%) were also accompanied by microtia in ECM. Raposo et al 15 showed that the ear malformations (93.1%) followed by mandible (59.8%) and facial nerve (10.8%) abnormalities were the most common CFM. Among patients, 37.2% had ECM involvement, mainly in vertebrae (20%), heart (11%), and limbs (9.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Heart malformation (15.3%), spine, chest, limb, and finger malformations (7.4%) were also accompanied by microtia in ECM. Raposo et al 15 showed that the ear malformations (93.1%) followed by mandible (59.8%) and facial nerve (10.8%) abnormalities were the most common CFM. Among patients, 37.2% had ECM involvement, mainly in vertebrae (20%), heart (11%), and limbs (9.8%).…”
Section: Discussionmentioning
confidence: 99%
“…This condition primarily affects the ear, mandible, tongue, face, and larynx ( Caron, Pluijmers, Wolvius, et al, 2017 ; Carvalho et al, 1999 ; Grabb, 1965 ; Poswillo, 1988 ). Eye, vertebral, and other extracraniofacial anomalies may also be present ( Caron, Pluijmers, Wolvius, et al, 2017 ; Raposo et al, 2022 ; Renkema et al, 2017 , 2018 ; Rooijers et al, 2020 ; Yang et al, 2016 ). Because of the complex presentation of both anatomic and functional findings, multidisciplinary craniofacial care throughout childhood is recommended for children with CFM ( Heike et al, 2013 ; Ronde et al, 2023 ; Vong & Funamura, 2018 ).…”
mentioning
confidence: 99%